Efeitos do ciclo de vida das empresas no matching e na qualidade dos accruals - Bandeira, Ana Mariella (2022)
This study aimed to analyse the effects of life cycle stages on matching and on the quality of accruals in publicly traded Brazilian companies. The stages of the life cycle are identified using, the methodology developed by Dickinson (2011), based on the signs of the company's cash flows, which classify the stages through dummy variables. The comparison of income with expenses was measured using the model of Dichev and Tang (2008) and the quality of accruals using the model of Dechow and Dichev (2002). The sample of this work is composed of 398 publicly traded Brazilian companies listed on B3 during the year 2010 to 2021. The effects of life cycle stages on matching and on the quality of accruals were verified by linear regressions multiples by ordinary least squares, controlling for sector and year fixed effects and identifying life cycle stages through dummies. Based on the methodology design, the results indicate that: i) for the original matching model, when run by life cycle, the explanatory power of the model varies in greater (lesser) intensity in the maturity stage (decline). For the accruals quality model, two metrics were used, and for the working capital accrual considering the depreciation when run by life cycle, the coefficients vary in greater (lesser) intensity in the maturity stage (decline) and for the accrual of working capital the coefficient varies more intensely in the decline stage; ii) for the life cycle interaction with the variables of the matching model, no significant results were found and for the quality model of working capital accruals, evidence was found that the interaction of the maturity stages (introduction) increases (worse) the quality of accruals considering current cash flow; and iii) the model that uses the residuals of the models in absolute values and the standard deviation did not show significance. The results suggest that there are effects of lesser or greater intensity of life cycle stages on matching and on the quality of accruals. The main contributions of the study are to improve the understanding of information from the joint analysis of accounting and life cycle data, expanding perceptions about performance and evaluation